God created the integers : the mathematical breakthroughs that changed history - Hawking, S. W. (Stephen W.) (Philadelphia : Running Press, 2007)
Bestselling author and physicist Hawking explores the "masterpieces" of mathematics, 25 landmarks spanning 2,500 years and representing the work of 15 mathematicians, including Augustin Cauchy, Bernard Riemann, and Alan Turing.
Euclid (c.325 BC-265 BC) -- Archimedes (287 BC-212 BC) -- Diophantus (third century AD) -- René Descartes (1596-1650) -- Isaac Newton (1642-1727) -- Leonhard Euler (1707-1783) -- Pierre Simon de Laplace (1749-1827) -- Jean Baptiste Joseph Fourier (1768-1830) -- Carl Friedrich Gauss (1777-1855) -- Augustin-Louis Cauchy (1789-1857) -- Augustin-Louis Cauchy (1789-1857) -- János Bolyai (1802-1860) -- Évariste Galois (1811-1832) -- George Boole (1815-1864) -- George Friedrich Bernhard Riemann (1826-1866) -- Karl Weierstrass (1815-1897) -- Richard Julius Wilhelm Dedekind (1831-1916) -- Georg Cantor (1845-1918) -- Henri Lebesgue (1875-1941) -- Kurt Gödel (1906-1978) -- Alan Mathison Turing (1912-1954).
Includes bibliographical references and index.
Keywords: Mathematics -- History; Mathematicians -- Biography